Impacto de la economía naranja en la producción y balanza comercial de colombia para el periodo 2017-2020 (2022)
This document analyzes the economic model of the orange economy, implemented in 2018 by President Iván Duque Márquez, verifying its impact on Colombia's GDP and trade balance.